Human Resource Competence, Work Ability, Workload, and Employee Performance in a Local Government Agency - Hakim, Abdul; Raldin; Nur, Muh. (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
Examining employee performance in government agencies is crucial, as it plays a pivotal role in determining the quality of government task execution and public service delivery. This study aims to analyze the influence of human resource competence, work ability, and workload on employee performance at the National Unity and Politics Agency of North Konawe Regency. A quantitative approach with a survey design was employed. The study population—which also served as the sample—consisted of 49 employees selected via a census technique. Data were collected using a structured questionnaire and analyzed through descriptive statistics and multiple linear regression. The results indicate that human resource competence, work ability, and workload simultaneously exert a positive and significant influence on employee performance (F = 570.496; p < 0.001), with an R² value of 0.974. Individually, human resource competence (B = 0.435; t = 6.272; p < 0.001), work ability (B = 0.427; t = 7.313; p < 0.001), and workload (B = 0.266; t = 8.237; p < 0.001) all demonstrated a positive and significant effect. The research model exhibits a very strong relationship (R = 0.987) and explains 97.4% of the variation in employee performance.